Non-ST elevation myocardial infarction secondary to carbon monoxide intoxication - Danuta Jankowska; Venkataraman Palabindala; Sohail Abdul Salim (Greater Baltimore Medical Center, 2017)
Carbon monoxide poisoning has been documented in literature to cause severe neurological and tissue toxicity within the body. However, cardiotoxicity is often overlooked, but not uncommon. Previous research studies and case reports have revealed a significant relationship between carbon monoxide intoxication and myocardial ischemic events. We report a case of a 48-year-old male, who was exposed to severe smoke inhalation due to a house fire and subsequently developed a non-ST elevation myocardial infarction. Ischemic changes were evident on electrocardiogram, which demonstrated T-wave inversion in lead III and ST-segment depression in leads V4-V6. Elevated cardiac enzymes were also present. After standard treatment for an acute cardiac event, the patient fully recovered. This case demonstrates that myocardial ischemic changes due to carbon monoxide poisoning may be reversible if recognized in early stages and treated appropriately, thus reminding physicians that a proper cardiovascular examination and diagnostic testing should be performed on all patients with carbon monoxide poisoning. Abbreviations: NSTEMI: Non-ST elevation myocardial infarction